METAPHOR DEALING WITH HUMAN NATURE IN WILLIAM BLAKEâ€™S â€œA POISON TREEâ€ - Etika Ully Amrina; Eko Budi Setiawan; Arielia Yustisiana (Universitas Katolik Widya Mandala Surabaya, 2017)
This research is aimed to describe the metaphor dealing with human nature in thepoem â€œA Poison Treeâ€, and to reveal the metaphor constituting the human naturein the poem. This is a library research in which all the data and the theories weretaken from written forms including internet browsing. The theories used in thisstudy are the theories of figures of speech, metaphor, meaning and symbol.Moreover, structural approach, formalistic approach and psychological approachare applied to decide the strategy in analyzing the metaphor and symbols found inthe poem. The analysis shows that: (1) there are two metaphor of human natureanalyzed in this research, they are metaphor related to feeling and metaphorrelated to human characteristics. Metaphor related to characteristics is divided intotwo main discussions namely individual and social creatures. Furthermore, thereare two symbols of human nature namely anger and karma.